Evapotranspiración máxima y respuesta del mani (Arachis Hypogaea L.) a tres módulos de riego (1997)
An experiment was carried out at the Agricultural Research Center "Nataima" to study the maximum evapotranspiration (ETM) of groundnut (Arachis hypogaea L.) var. Tatui-76, by using a lysimeter, model THORNTHWAITE. It was found that growth periods determine the values of ETM; maximum average values of 5.16 mm/day at the begining (VE Ri ) and 1.35 mm/day at the end (R5) of the growth period. The blioclimatic coefficient, Km, (ETM/Ev, relationship between ETM and pan evaporation, Ev) fluectuated from 0.24 to 1.35, depending on the crop stage. Surrounded the lysimeter, different irrigation treatments taken as soil available water depletion factors were evaluated as follows: 1) 30%, 2) 60%, 3) 90% and 4) Non-irrigation treatment. According to the best, yield, irrigation water should be applied when 60% of the soil available water has depleted.